From Explorer to Leader: The DSRES Index as a Framework for Design Science Research Maturity - Oliveira Dias, Murillo; Silva Junior, Dercio Santiago (Advances in Social Sciences Research Journal, 2026)
This article introduces the Design Science Research Effectiveness Index (DSRES Index), a methodological innovation for evaluating the maturity and impact of managerial design research. Building on the validated DSRES Scale, the Index integrates five dimensions—Rigor, Utility, Knowledge, Engagement, and Evaluation—into a composite measure of research effectiveness, with weights informed by confirmatory factor analysis and theoretical reasoning. In addition to measurement, the study advances a typology that distinguishes four organizational maturity profiles: Explorer, Developer, Integrator, and Leader. Each profile reflects specific characteristics and challenges, and outlines pathways for progression. A distinctive contribution of this work lies in the inclusion of managerial recommendations and interpretive insights, which transform the typology into a practical tool for guiding organizational development. By offering a valid and replicable assessment method, the DSRES Index enables comparative studies, strengthens design-oriented projects, and supports the integration of scientific evidence into managerial practice.